Methylation panel is a diagnostic biomarker for Barrett's oesophagus in endoscopic biopsies and non-endoscopic cytology specimens. Issue 11 (30th October 2017) - Chettouh, Hamza; Mowforth, Oliver; Galeano-Dalmau, Núria; Bezawada, Navya; Ross-Innes, Caryn; MacRae, Shona; Debiram-Beecham, Irene; O'Donovan, Maria; Fitzgerald, Rebecca C
Abstract : Objective: Barrett's oesophagus is a premalignant condition that occurs in the context of gastro-oesophageal reflux. However, most Barrett's cases are undiagnosed because of reliance on endoscopy. We have developed a non-endoscopic tool: the Cytosponge, which when combined with trefoil factor 3 immunohistochemistry, can diagnose Barrett's oesophagus. We investigated whether a quantitative methylation test that is not reliant on histopathological analysis could be used to diagnose Barrett's oesophagus. Design: Differentially methylated genes between Barrett's and normal squamous oesophageal biopsies were identified from whole methylome data and confirmed using MethyLight PCR in biopsy samples of squamous oesophagus, gastric cardia and Barrett's oesophagus. Selected genes were then tested on Cytosponge BEST2 trial samples comprising a pilot cohort (n=20 cases, n=10 controls) and a validation cohort (n=149 cases, n=129 controls). Results: Eighteen genes were differentially methylated in patients with Barrett'soesophagus compared with squamous controls. Hypermethylation of TFPI2, TWIST1, ZNF345 and ZNF569 was confirmed in Barrett's biopsies compared with biopsies from squamous oesophagus and gastric cardia (p<0.05). When tested in Cytosponge samples, these four genes were hypermethylated in patients with Barrett's oesophagus compared with patients with reflux symptoms (p<0.001). The optimum biomarker to diagnose Barrett's oesophagus was TFPI2 with a sensitivity and specificity of 82.2% and 95.7%, respectively. Conclusion: TFPI2, TWIST1, ZNF345 and ZNF569 methylation have promise as diagnostic biomarkers for Barrett's oesophagus when used in combination with a simple and cost effective non-endoscopic cell collection device.